Delik Terhadap Keamanan Negara (Makar) Di Indonesia (Suatu Analisis Yuridis Normatif pada Studi Kasus Sultan Hamid II) - -, Anshari (UI Scholars Hub, 2018)
This research is normative study (doctriner) to crime against state security (Makar) in Indonesia, this criminal act compared with a study to one case, which is accusation about “makar” or “rebellion” to Sultan Hamid II during 1950-1953. The definition from criminal act aginst state security regulated in Section One Book Two Criminal Code (KUHP). Core from this criminal act that forbidden is that Makar (Aanslag) and Rebellion (Opstand). In practical also in Indonesian history, often found cases about law violation in Indonesia that are actually not neccessarily include violation about attempt against state security. But the goverment as political leader, to criminal offender often charged with articles about criminal act against state security or rebellion. Study to see the implementation on regulation about makar, then can see by case study to controversial case Sultan Hamid II during 1950-1953. Which is can see country objectivity in judging a makar case.